Whole genome sequencing of toxigenic Clostridium difficile in asymptomatic carriers: insights into possible role in transmission. Issue 2 (June 2019) - Halstead, F.D.; Ravi, A.; Thomson, N.; Nuur, M.; Hughes, K.; Brailey, M.; Oppenheim, B.A.
Summary: Background: Estimates of the prevalence of asymptomatically carried Clostridium difficile in elderly patients in long-term care range from 0% to 51%. Asymptomatic carriage is possibly a risk factor for the development of infection, and there is ongoing debate surrounding the role of asymptomatic carriage in transmission. Aim: To investigate the prevalence of asymptomatic carriage amongst patients residing in intermediate care (bedded) facilities (ICBFs), and to investigate whether asymptomatically carried C. difficile strains contribute to nosocomial C. difficile infection (CDI). Methods: Stools were collected from eligible asymptomatic patients in ICBFs, and a subset was also processed from symptomatic patients accessing primary or secondary care outside of ICBFs. All samples were cultured for C. difficile, and resulting colonies were processed through whole genome sequencing. Findings: In total, 151 asymptomatic patients were sampled, 22 of which were positive for C. difficile through stool culture, representing a carriage rate of 14.6%. Sequencing of these isolates, alongside 14 C. difficile polymerase chain reaction and culture-positive isolates from symptomatic individuals, revealed that all asymptomatic patients were carrying toxigenic C. difficile, and these strains were genetically similar to those from symptomatic patients. Conclusion: This small study of asymptomatic carriage revealed a rectal asymptomatic carriage rate of 14.6% in patients nursed in ICBFs, and a high level of genetic similarity of these strains to those recovered from symptomatic patients. As such, asymptomatic carriers may be important for the transmission of symptomatic CDI, although it is acknowledged that this study was small, and many other factors govern whether C. difficile is carried asymptomatically or causes symptoms.